Settlement of Inheritance Distribution According to Mare Customary Law in Maybrat Regency - Marselus Nauw; Muhammad Ali; Hasriyanti Hasriyanti; Rajab Lestaluhu (Journal of Law Justice (JLJ), 2025)
This study aims to analyze the inheritance distribution system according to the customary law of the Mare Tribe in Maybrat Regency, Southwest Papua, with a focus on the role of the kinship system and the principle of inheritance based on lineage. The method used in this study is an empirical approach with data collection through interviews and document studies. Primary data was obtained from interviews with local indigenous communities and regional officials, while secondary data was collected through literature studies covering regional regulations, books, and relevant scientific articles. Data analysis was conducted qualitatively using descriptive methods to describe the practice of inheritance distribution in the Mare tribe community. The novelty of this research lies in its in-depth focus on the customary inheritance distribution system in Southwest Papua, particularly in the Mare District, which still maintains the tradition of primogeniture and the Tua Marga principle. This system shows that the first child of the family, especially the male, has the primary right to inheritance consisting of land and natural resources. This study also reveals the importance of the patrilineal kinship system in determining heirs and the dominant role of men in the management of inheritance. The results show that the inheritance system in the Mare tribe community still adheres to old traditions, where the distribution of inheritance is carried out from generation to generation, taking into account the position of Tua Marga as the main heir. However, this system also allows women to inherit property under certain circumstances, such as when there are no male children in the family. The conclusion of this study is that the customary law of the Mare tribe remains relevant in regulating the distribution of inheritance, taking into account social status in the lineage and the role of men in the management of inherited property.